Status of Wild Orchids in the Mountain Ranges of Pilar, Capiz: Basis for Conservation - Obligar, Philomel Innocent (Contemporary Journal of Applied Sciences, 2024)
Because of their inherent beauty, orchids are highly valued. Of all blooming plants, it is the most evolved; to flourish in a particular habitat, it requires ideal circumstances. An ecosystem is said to be healthy and functional if orchids are found there. Genetic variety loss is just as much of an issue as species extinction. Thus this study was conducted with the aim of assessing the abundance, endemism, and conservation status of wild orchids in the mountain ranges of Pilar, Capiz. This study was conducted at 3 mountainous area in Piar, namely Mt. Agudo, Mt. San Silvestre and Mt. Tabun-aca. Walk transect method and opportunistic sampling technique following a trail was used. There were 7 species of wild orchids belonging to 6 genera recorded in the mountain ranges of Pilar.Three species were found to be widespread endemic, 3 were found to be Philippine endemic and 3 were endangered species, 3 vulnerable and 1 neutralized.